(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2024)
This article examines the German-language literary achievements of Ukrainian authors and their translation activities between German and Ukrainian languages. The analysis focuses on two prominent figures of Ukrainian literature - Panteleimon Kulish and Ivan Franko, who are considered founders of the Ukrainian translation school. The study traces the traditions of translating German classical literature within the Ukrainian context and determines the character and purpose of translation activities of these outstanding literary figures. P. Kulish’s translation work is analyzed using W. Goethe’s ballad "Erlkönig" as an example, highlighting his extraordinary talent despite being self-taught in foreign languages. The article examines I. Franko’s multifaceted creative legacy as a writer, poet, translator, linguist, and public figure, defining three spheres of his translation activity: literary texts, scientific works, and apocryphal literature. A comparative analysis of translations of Goethe’s "Erlkönig" by P. Kulish, B. Hrynchenko, and M. Rylsky illustrates the evolution from ``old’’ to ``new’’ masters of Ukrainian translation, revealing differences in interpretation of imagery, emotional tone, and mood transfer from the original text.